Neruda y las campanas - Carrasco, Eduardo (Anales de la Universidad de Chile, 1999)
The author begins with a statement by Neruda: "I am the poet of the wild informality of the unknown", in order to examine then the metaphor of the bell, emerging in different moments of the poet's work. This metaphor reveals Neruda's vision about his own poetry, and the essences of the poetic speaking, as an approach to the limits of what can be expressed, and as the territory of unity where human being and that "informality wild of the unknown" .